Markers of bone turnover for the prediction of fracture risk and monitoring of osteoporosis treatment: a need for international reference standards. - Vasikaran, S; Eastell, R; Bruyère, O; Foldes, A; Garnero, P; Griesmacher, A; McClung, M; Morris, H; Silverman, S; Trenti, T; Wahl, D; Cooper, C; et al. (2011)
The International Osteoporosis Foundation (IOF) and the International Federation of Clinical Chemistry and Laboratory Medicine (IFCC) recommend that a marker of bone formation (serum procollagen type I N propeptide, s-PINP) and a marker of bone resorption (serum C-terminal telopeptide of type I collagen, s-CTX) are used as reference analytes for bone turnover markers in clinical studies.